As relações entre informação, linguagem e símbolo: a filosofia da Ciência da Informação entre a realidade e idealidade - Silva, Giovani Miguez da (2016)
This dissertation addresses, from a philosophical reflection, the relationship between the concepts of information, language and symbol. The research sought to understand the approaching margins of these concepts from a perspective that aimed to predict the Information Science as an episteme between reality and ideality. In the development of this work, it was sought to test, through a hermeneutics applied to three distinct approaches, arising from the thought of Ernst Cassirer, Xavier Zubiri and Rafael Capurro, two basic hypotheses: (1) if the Information Science can be considered a Hermeneutics Science as sub-discipline of Rhetoric (traditional capurrian hypothesis) and (2) if the Information Science Philosophy can be considered a Philosophical Anthropology. For this, the study reviewed the general aspects of the information concept, established some conceptual relationships between information, language and symbol, toured the epistemological paradigms (physicalist, cognitive and social) and philosophical (representationist, emitter-channel-receiver and platonic) identified by Rafael Capurro, and discussed the core concepts of "philosophy of symbolic forms", from Ernest Cassirer, and the "philosophy of intelligence and reality," from Xavier Zubiri. When reviewing the concepts of Cassirer and Zubiri, the reflection aimed to relate the possible conceptual approaches that confirmed the hypotheses. The work presented as a conclusion the argument that the social paradigm favors both the deployment of the Information Science as a hermeneutic science and the Information Science Philosophy as a philosophical anthropology. It was considered, therefore, that in a philosophical aspect, the Information Science, as a hermeneutic-rhetorical science, on the one hand, gets closer to Cassirer in a representationist approach; on the other hand, to Zubiri, in a platonic approach. The study also suggested some future directions to be explored: the development of studies about information and symbolic and the research of an informational ethics from a philosophical anthropology.